2022
DOI: 10.3389/fchem.2022.922110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors Targeting Multiple Janus Kinases From Zanthoxylum simulans Mediate Inhibition and Apoptosis Against Gastric Cancer Cells via the Estrogen Pathway

Abstract: Janus kinases (JAKs) play a key role in subtly regulating proliferation, apoptosis, and differentiation of cancer cells, and their inhibitors are actively sought as new drug leads. By developing JAKs based affinity ultrafiltration method coupled with LC/Q-TOF-MS in order to discover selective JAKs inhibitors from total quaternary alkaloids (QAs) from Zanthoxylum simulans, peak 19 (Berberine) and peak 21 (Chelerythrine) were revealed to exhibit notable selectivity on JAK1, JAK2, and JAK3 over Tyk2. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…11 In addition, many studies have demonstrated the anticancer effects of this medicinal herb such as stomach cancer, prostate cancer, leukemia, etc. 12,13 According to the study of Ha Do Thi et al, Z. simulans seed extract showed cytotoxicity to HT-1080 with an IC50 value of 7.1 μg/mL. The leaf extract of Z. simulans also could inhibit many cancer cell lines such as A549, Huh-7, and HT-1080 with IC50 values of 2.7 ± 0.2, 3.2 ± 0.0, 2.8 ± 0.0 μg/mL, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, many studies have demonstrated the anticancer effects of this medicinal herb such as stomach cancer, prostate cancer, leukemia, etc. 12,13 According to the study of Ha Do Thi et al, Z. simulans seed extract showed cytotoxicity to HT-1080 with an IC50 value of 7.1 μg/mL. The leaf extract of Z. simulans also could inhibit many cancer cell lines such as A549, Huh-7, and HT-1080 with IC50 values of 2.7 ± 0.2, 3.2 ± 0.0, 2.8 ± 0.0 μg/mL, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This plant has been used in traditional medicine as a medicine mainly used to relieve pain, anti‐inflammation, and anti‐malarial 11 . In addition, many studies have demonstrated the anti‐cancer effects of this medicinal herb such as stomach cancer, prostate cancer, leukemia, etc 12,13 . According to the study of Ha Do Thi et al., Z. simulans seed extract showed cytotoxicity to HT‐1080 with an IC50 value of 7.1 µg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further studies should be carried out to further explore the bio-active substances and potential mechanisms. Because of multiple substances detected in QAs, it is not easy to figure out the bio-active ingredients and illustrate the potential mechanisms ( Tian et al, 2022 ). Compound isolation combined with activity analysis is a traditional way to discover potential prodrugs, but the time-consuming method may not match the need of improving research efficiency ( Tian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of multiple substances detected in QAs, it is not easy to figure out the bio-active ingredients and illustrate the potential mechanisms ( Tian et al, 2022 ). Compound isolation combined with activity analysis is a traditional way to discover potential prodrugs, but the time-consuming method may not match the need of improving research efficiency ( Tian et al, 2022 ). Ultrafiltration targeting of enzymes has been reported to fish potential bio-active candidates in recent years ( Tian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation